Capacidade de carga de estacas da fundação da nova ponte sobre o Rio Zambeze. Previsões e verificação através de ensaios de carga pelo método de Osterberg - A. Viana da Fonseca (2008)
The evaluation of pile bearing capacity is dependent on the interpretation of the pile headload-settlement curve and the determination of the shaft and toe resistances in careful andwell instrumented tests, making possible to calibrate design methods from load transfer curvein depth for progressive loading levels. In the New Zambezi Bridge (Mozambique, Caia - Chimuara) deep foundations have been designed taking into consideration differentmethodologies: methods based in SPT data (Reese & O'Neill) and methods based in CPT data(Bustamante & Giasenelli, 1982), giving rise to some scatter in final results. For the completeand trustful solution, static load tests in piles were executed using Osterberg test method, inorder to obtain a simple way to evaluate shaft load transfer and define the applicability ofeach empirical methodology. Results of this comparative analysis are presented and somesuggestions are presented for regional practice.